## Results (displaying matches 1-50 of 1328) Next

Label Class Equation Sato-Tate $$\overline{\Q}$$-simple $$\GL_2$$ Rank*
1070.a.2140.1 1070.a $$y^2 + (x^3 + 1)y = x^3 - x$$ $\mathrm{USp}(4)$ 1
1094.a.2188.1 1094.a $$y^2 + (x^3 + 1)y = x^4 - x^2$$ $\mathrm{USp}(4)$ 1
1198.a.2396.1 1198.a $$y^2 + (x^3 + 1)y = -x$$ $\mathrm{USp}(4)$ 1
1383.a.4149.1 1383.a $$y^2 + y = x^5 + x^4$$ $\mathrm{USp}(4)$ 1
1385.a.6925.1 1385.a $$y^2 + y = x^5 + 3x^4 + 3x^3 - x$$ $\mathrm{USp}(4)$ 1
1636.a.6544.1 1636.a $$y^2 + (x^3 + x)y = -x^4 - x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 1
1664.a.3328.1 1664.a $$y^2 + xy = x^6 - 2x^5 - x^4 + 3x^3 - x$$ $\mathrm{USp}(4)$ 1
1791.a.5373.1 1791.a $$y^2 + y = 3x^5 + 6x^4 + 2x^3 - x^2$$ $\mathrm{USp}(4)$ 1
1899.a.5697.1 1899.a $$y^2 + (x^3 + 1)y = -x^5 + x^4 - 3x + 2$$ $\mathrm{USp}(4)$ 1
1952.a.15616.1 1952.a $$y^2 + (x^3 + x)y = x^3 - x$$ $\mathrm{USp}(4)$ 1
1982.a.63424.1 1982.a $$y^2 + (x + 1)y = -x^5 + x^4 - x^3 + x^2$$ $\mathrm{USp}(4)$ 1
2102.a.33632.1 2102.a $$y^2 + (x + 1)y = x^5 + 2x^4$$ $\mathrm{USp}(4)$ 1
2218.a.70976.1 2218.a $$y^2 + (x^3 + x)y = -2x^4 + 2x^2 - x + 1$$ $\mathrm{USp}(4)$ 1
2312.a.4624.1 2312.a $$y^2 + xy = x^6 - 2x^4 - x^3 + x^2 + x$$ $\mathrm{USp}(4)$ 1
2312.a.18496.1 2312.a $$y^2 + (x + 1)y = x^6 - x^4$$ $\mathrm{USp}(4)$ 1
2432.a.19456.1 2432.a $$y^2 + (x + 1)y = x^6 + 2x^5 + 2x^2 + x$$ $\mathrm{USp}(4)$ 1
2528.a.20224.1 2528.a $$y^2 + (x^2 + 1)y = x^5 - x$$ $\mathrm{USp}(4)$ 1
2602.a.41632.1 2602.a $$y^2 + (x^3 + x)y = x^5 - 2x^3 + 6x + 4$$ $\mathrm{USp}(4)$ 1
2950.a.472000.1 2950.a $$y^2 + (x^3 + 1)y = x^5 + x^4 + x^3 + 2x^2 - x - 1$$ $\mathrm{USp}(4)$ 1
2985.a.134325.1 2985.a $$y^2 + y = x^5 + x^4 + 2x^2$$ $\mathrm{USp}(4)$ 1
3003.b.819819.1 3003.b $$y^2 + (x^2 + 1)y = x^5 + 4x^4 + 3x^3 + x$$ $\mathrm{USp}(4)$ 1
3008.a.24064.1 3008.a $$y^2 + (x^2 + 1)y = x^5 - 2x^3 + x$$ $\mathrm{USp}(4)$ 1
3105.b.27945.1 3105.b $$y^2 + (x^2 + x + 1)y = x^5 + 3x^4 - 4x^2$$ $\mathrm{USp}(4)$ 1
3142.b.201088.1 3142.b $$y^2 + (x^3 + x)y = x^5 + 6x^2 + 10x + 4$$ $\mathrm{USp}(4)$ 1
3153.a.9459.1 3153.a $$y^2 + y = x^5 + 2x^4 - 3x^3 - x^2 + x$$ $\mathrm{USp}(4)$ 1
3226.a.12904.1 3226.a $$y^2 + (x + 1)y = -x^5 - 4x^4 - 4x^3$$ $\mathrm{USp}(4)$ 1
3298.b.844288.1 3298.b $$y^2 + (x^3 + x)y = x^5 + 3x^4 + 3x^3 + x + 1$$ $\mathrm{USp}(4)$ 1
3327.a.9981.1 3327.a $$y^2 + (x^3 + x^2 + x + 1)y = -x^4 - x^3 - 2x$$ $\mathrm{USp}(4)$ 1
3328.b.13312.1 3328.b $$y^2 + (x + 1)y = x^6 - x^3 - x^2$$ $\mathrm{USp}(4)$ 1
3578.a.57248.1 3578.a $$y^2 + (x + 1)y = -x^5 + 2x^4 + 2x^3$$ $\mathrm{USp}(4)$ 1
3622.a.463616.1 3622.a $$y^2 + (x^3 + 1)y = -x^5 + x^3 + 3x^2 - 2x - 1$$ $\mathrm{USp}(4)$ 1
3644.b.58304.1 3644.b $$y^2 + (x^3 + 1)y = x^5 - x$$ $\mathrm{USp}(4)$ 1
3675.a.385875.1 3675.a $$y^2 + (x^3 + x^2)y = x^5 + 2x^4 + x^2 + x - 6$$ $\mathrm{USp}(4)$ 1
3712.b.118784.1 3712.b $$y^2 + (x^3 + x^2 + x + 1)y = x^5 - x$$ $\mathrm{USp}(4)$ 1
3746.c.239744.1 3746.c $$y^2 + (x + 1)y = -x^5 + 2x^4 - 2x^3 + x$$ $\mathrm{USp}(4)$ 1
3788.b.242432.1 3788.b $$y^2 + (x^3 + 1)y = x^5 + x^4 - x^2 - 2x$$ $\mathrm{USp}(4)$ 1
3807.a.925101.1 3807.a $$y^2 + y = x^5 + 7x^4 + 7x^3 + 4x^2 + x$$ $\mathrm{USp}(4)$ 1
3984.a.47808.1 3984.a $$y^2 + (x + 1)y = -2x^5 + x^3$$ $\mathrm{USp}(4)$ 1
4150.a.41500.1 4150.a $$y^2 + (x^2 + x + 1)y = x^6 + 3x^5 + 2x^4 - x - 1$$ $\mathrm{USp}(4)$ 1
4252.a.68032.1 4252.a $$y^2 + (x^3 + 1)y = x^4 - x^2 - x$$ $\mathrm{USp}(4)$ 1
4276.a.273664.1 4276.a $$y^2 + (x^2 + x + 1)y = 4x^5 + 8x^4 + 4x^3$$ $\mathrm{USp}(4)$ 1
4580.a.293120.1 4580.a $$y^2 + (x^3 + 1)y = x^5 - x^4 - 4x^3 + x^2 + 2x$$ $\mathrm{USp}(4)$ 1
4706.a.150592.1 4706.a $$y^2 + (x + 1)y = -x^5 + 2x^3 + 2x^2$$ $\mathrm{USp}(4)$ 1
4992.a.119808.1 4992.a $$y^2 + (x + 1)y = x^6 - 2x^5$$ $\mathrm{USp}(4)$ 1
4992.c.958464.1 4992.c $$y^2 + (x^2 + 1)y = 3x^5 + x^4 - x$$ $\mathrm{USp}(4)$ 1
5004.a.960768.1 5004.a $$y^2 + (x^3 + 1)y = -2x^4 + 2x^3 - 2x + 2$$ $\mathrm{USp}(4)$ 1
5012.c.320768.1 5012.c $$y^2 + (x^3 + 1)y = x^5 - 2x^4 + 2x^2 - x$$ $\mathrm{USp}(4)$ 1
5103.a.15309.1 5103.a $$y^2 + x^3y = x^5 - 3x^3 - x^2 + 3x + 2$$ $\mathrm{USp}(4)$ 1
5184.c.995328.1 5184.c $$y^2 + y = 4x^5 - x^3 - x^2$$ $\mathrm{USp}(4)$ 1
5416.a.173312.1 5416.a $$y^2 + (x + 1)y = x^6 - x^2$$ $\mathrm{USp}(4)$ 1
Next